2015
DOI: 10.1007/s00204-015-1518-5
|View full text |Cite
|
Sign up to set email alerts
|

Progress and future of in vitro models to study translocation of nanoparticles

Abstract: The increasing use of nanoparticles in products likely results in increased exposure of both workers and consumers. Because of their small size, there are concerns that nanoparticles unintentionally cross the barriers of the human body. Several in vivo rodent studies show that, dependent on the exposure route, time, and concentration, and their characteristics, nanoparticles can cross the lung, gut, skin, and placental barrier. This review aims to evaluate the performance of in vitro models that mimic the barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(79 citation statements)
references
References 233 publications
(329 reference statements)
0
79
0
Order By: Relevance
“…Translocation of TiO 2 NPs in sizes 18, 40-50, 120 and 130 nm were below the detection limit in the majority of the studies (Braakhuis et al 2015). This rate appeared realistic when compared to animal data.…”
Section: Oral Routementioning
confidence: 73%
“…Translocation of TiO 2 NPs in sizes 18, 40-50, 120 and 130 nm were below the detection limit in the majority of the studies (Braakhuis et al 2015). This rate appeared realistic when compared to animal data.…”
Section: Oral Routementioning
confidence: 73%
“…In an immortalized mouse cerebral endothelial cell line, the bEnd3 monolayer, it was previously found that the permeability of different solutes (with MW up to 70000) is linearly decreased as solute Stokes radius increases, and that the permeability of quaternary ammonium b-cyclodextrin nanoparticles (QAbCD) with varying zeta potential values, ranging from À11 to +14 is different; the positively charge QAbCD's having higher permeability's (Yuan et al, 2010). In a recent review about in vitro models used to study the translocation of nanoparticles (Braakhuis et al, 2015), particle size is mentioned to affect the translocation of nanoparticles across several cellular models, such as rat alveolar epithelial cell monolayers, as well as cellular models of the placental and intestinal barrier. In fact it is well known that the size and charge of nanoparticles has a profound effect on their (in vivo/ ex-vivo) intestinal transport (Araujo et al, 2014;Jani et al, 1990Jani et al, , 1989.…”
Section: Discussionmentioning
confidence: 99%
“…While cell cultures grown in petri dishes have been traditionally conducted under immersed conditions, those at an ALI are known to increase monolayer integrity 120,123,126,129 (measured by trans-epithelial electrical resistance, TEER), contribute to well differentiated morphology in primary cells, 130,131 and increase surfactant secretion for AEC II cells 126,129 . Hence, culture methods at an ALI have been increasingly attractive over the past years, 118,132 emphasizing such method as a favourable platform to investigate the epithelial barrier at large 126,129 as well as cytotoxicity in the context of inhaled xenobiotics 132–136 and drug transport 137–139 …”
Section: Recreating Airway Barrier Models In Vitromentioning
confidence: 99%